LONG-TERM OUTCOME OF RIGHT HEPATECTOMY WITH SELECTIVE CONTROL OF THE RIGHT HEPATIC PEDICLE FOR HEPATOCELLULAR CARCINOMA AT VIETNAM NATIONAL CANCER HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the results of right hepatectomy with selective control of the right hepatic pedicle for hepatocellular carcinoma (HCC). Subjects and methods: Retrospective descriptive study on 131 patients undergoing right hepatectomy with selective control of the right hepatic pedicle for HCC at the Department of Hepatobiliary and Pancreatic Surgery, Vietnam National Cancer Hospital, from January 2020 to December 2024. Results: The mean age was 55.2 ± 12.2 years; 78.6% were HBsAg-positive; tumors > 5 cm accounted for 76.3%; solitary tumors for 87.8%; and moderately differentiated tumors for 57.3%. Selective right pedicle control was achieved using the Takasaki approach in 85.5% of patients. No 30-day postoperative mortality was recorded. Mean overall survival was 55 ± 2.5 months, and mean disease-free survival was 43.3 ± 2.8 months. AFP > 400 ng/mL and tumor differentiation were associated with OS, whereas no statistically significant association was observed with DFS. Tumor size > 5 cm and tumor number were not significantly associated with OS or DFS. Conclusion: Right hepatectomy with selective control of the right hepatic pedicle is a safe and effective treatment for appropriately selected patients with HCC. The 5-year overall survival rate was 65,3%.
Keywords: hepatocellular carcinoma, right hepatectomy, selective control of the right hepatic pedicle.